2007
DOI: 10.1002/pros.20683
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate restriction, prostate cancer growth, and the insulin‐like growth factor axis

Abstract: BACKGROUND. Recent evidence suggests carbohydrate intake may influence prostate cancer biology. We tested whether a no-carbohydrate ketogenic diet (NCKD) would delay prostate cancer growth relative to Western and low-fat diets in a xenograft model. METHODS. Seventy-five male SCID mice were fed a NCKD (84% fat-0% carbohydrate-16% protein kcal), low-fat (12% fat-72% carbohydrate-16% protein kcal), or Western diet (40% fat-44% carbohydrate-16% protein kcal). Low-fat mice were fed ad libitum and the other arms fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 35 publications
(46 reference statements)
10
135
5
2
Order By: Relevance
“…17 In animals, dietary-induced increased serum IGF-I and insulin levels are associated with increased PC growth. [18][19][20] Moreover, elevated insulin levels are also linked with BPH, another prostate-related disease. 21 Among men with PC, those with C-peptide concentrations (a marker of insulin) in the highest quartile had a 2.4-fold increased PC death vs men in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…17 In animals, dietary-induced increased serum IGF-I and insulin levels are associated with increased PC growth. [18][19][20] Moreover, elevated insulin levels are also linked with BPH, another prostate-related disease. 21 Among men with PC, those with C-peptide concentrations (a marker of insulin) in the highest quartile had a 2.4-fold increased PC death vs men in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that a NCKD slows tumor growth across different models [11,12]. As such, we hypothesize that the lack of a dose-effect among low-carbohydrate diets and the overall benefit of low-carbohydrate diet are generalizable, though this requires formal testing in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…While traditionally a low fat diet was thought to be optimal, we previously hypothesized that a reduced carbohydrate diet was likewise beneficial [10]. In a prior study we found that mice consuming a no-carbohydrate ketogenic diet (NCKD) had increased overall survival and slower tumor growth, compared to mice on a western diet, a benefit not observed in mice consuming a low fat diet [11]. These findings were then replicated in a similar xenograft model with the finding that a low-fat diet was also beneficial [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, controversial results have also been reported about the role of high fat diet in carcinogenicity [71,72]. This is largely due to the complexity of the diet, not only the fat components such as SFA, MUFA, and PUFA may vary among people in different regions, but also other non-fat nutrients may also alter the function of fat.…”
Section: Dietary Lipids and Cancermentioning
confidence: 99%